1997
DOI: 10.1007/pl00003824
|View full text |Cite
|
Sign up to set email alerts
|

Piggy-back versus conventional technique in liver transplantation: report of a randomized trial

Abstract: Liver transplantation with preservation of the recipient vena cava (the "piggy-back" technique) has been proposed as an alternative to the traditional method. We performed a randomized study on 39 cirrhotic patients, 20 who underwent the piggy-back technique (group 1) and 19 the traditional method using venovenous bypass (group 2) to evaluate the feasibility and true advantages of the piggy-back technique compared to the traditional method. Two patients were switched to the conventional technique due to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
2
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 5 publications
3
75
2
7
Order By: Relevance
“…In a recent comparison of the two techniques, we demonstrated significantly lower blood transfusion requirements in patients in whom the ‘piggyback’ technique was used, compared with patients transplanted using the ‘classical’ technique [36]. Similar observations have been made by other groups [35]. …”
Section: Evolution Of Surgical Techniques To Minimize Blood Losssupporting
confidence: 71%
See 1 more Smart Citation
“…In a recent comparison of the two techniques, we demonstrated significantly lower blood transfusion requirements in patients in whom the ‘piggyback’ technique was used, compared with patients transplanted using the ‘classical’ technique [36]. Similar observations have been made by other groups [35]. …”
Section: Evolution Of Surgical Techniques To Minimize Blood Losssupporting
confidence: 71%
“…Although never formally proven by a randomized controlled trial, it has been suggested that venovenous bypass also results in a reduction of intraoperative blood loss [33]. Another important step forward has been the introduction of the so-called ‘piggyback’ technique [34, 35]. In contrast with the ‘classical’ technique of liver transplantation, in the piggyback technique the retrohepatic inferior vena cava (IVC) is not removed together with the native liver.…”
Section: Evolution Of Surgical Techniques To Minimize Blood Lossmentioning
confidence: 99%
“…The preservation of the recipient inferior vena cava (IVC) according to the piggy‐back technique (PB) is now used worldwide during orthotopic liver transplantation (OLT). Although several institutions use this technique as the habitual ones some reports have mentioned possible disadvantages of this technique: PB has been associated with an increased risk of suprahepatic IVC thrombosis or stenosis, venous congestion of the liver allograft, and an increased incidence of post‐transplant ascites 1,2 . All these complications may be related to a difficult venous outflow at the site of the anastomosis with the recipient IVC, this point being potentially the ‘Achille's heel’ of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Der venovenöse Bypass sollte eingesetzt werden, wenn diese Bedingungen nicht vorliegen [5,10]. Die Vorteile des Erhalts der V. cava beim Empfänger wurden vielfach beschrieben, vor allem zur Vermeidung des venovenösen Bypasses [3, 7 a, 9, 14], zur Verbesserung der hämodynamischen Stabilität [1] und zur verbesserten renalen Perfusion [3,8,9,15]. Durch die Anlage eines temporären portocavalen Shunt während der Cava-erhaltenden Lebertransplantation bleibt nicht nur die venöse Drainage der Nieren erhalten und das Blutungsrisiko der retrocavalen Dissektion herabgesetzt, sondern es wird auch die kardiovasculäre Stabilität erhöht und der intestinale Stauungsdruck vermindert [1,2,13].…”
Section: Diskussionunclassified